Assessment of spatial changes in Lake Karataş using remote sensing and GIS: ecological and hydrological transformation - Meltem Güneş Tigen; Osman Özcan (Journal of Freshwater Ecology)
Wetlands play a crucial role in maintaining hydrological balance, conserving biodiversity, and storing carbon. However, they are increasingly threatened by climate change, agricultural expansion, urbanization, and excessive water use. Lake Karataş, a critical wetland in Türkiye that supports diverse avian and aquatic species, has experienced significant hydrological changes in recent decades. This study examines the spatiotemporal changes in the lake’s surface area and its interaction with land use between 1985 and 2024 using remote sensing techniques. Landsat 5 TM and Landsat 8 OLI/TIRS summer imagery were analyzed to assess water surface changes using the MNDWI, NDVI, and NDMI indices. The results indicate that Lake Karataş, which covered 11.45 km2 in 1985, had completely dried up by 2024, leading to biodiversity loss and the disappearance of aquatic habitats. According to CORINE land use data, between 1990 and 2018, permanently irrigated areas expanded by 21.78%, while dry farming areas decreased by 14.39%. These land use changes coincide with a significant decline in lake water levels, confirming that agricultural expansion has been a major driver of ecosystem degradation. Temporal analysis shows that between 1985 and 2005, lake surface fluctuations were primarily influenced by climatic factors, as indicated by proportional trends in the NDMI, MNDWI, and NDVI indices. However, after 2005, anthropogenic activities, particularly the expansion of irrigated agriculture, became the dominant cause of lake desiccation. To protect the Lake Karataş ecosystem and ensure sustainable water management, it is essential to regulate irrigated agriculture and prioritize regionally adapted crop production models. Key strategies include promoting drought-resistant crops, implementing high-efficiency irrigation systems, and adopting sustainable water management policies. This study highlights the effectiveness of remote sensing in monitoring long-term wetland transformations and identifying their primary drivers.